APPLICATION D-OPTIMAL METHOD ON THE OPTIMIZATION OF FORMULATION OF KINTAMANI ARABICA COFFEE GEL (Coffea arabica L.) - Hendra Wijaya; I Putu Rizki Karisma Parta Wiratama; Pande Ketut Pramita Desna Putri; Kadek Sutri Ariyanthini; Elisabeth Angelina; Ni Kadek Devi Pradnya Andina; Putu Saradevi Naripradnya; Eka Indra Setyawan (Universitas Muhammadiyah Magelang, 2022)
Arabica coffee (Coffea arabica L.) kintamani is a superior agricultural product from Bali. Arabica coffee (Coffea arabica L.) contains many compounds, one of which is caffeine which is beneficial for health and beauty. This study aims to formulate kintamani arabica coffee beans into a gel dosage form. The optimization formula of kintamani arabica coffee bean gel was made using the D-Optimal method using a combination of HPMC and propylene glycol as observation variables and spreadability, pH, and viscosity of the gel preparation as experimental responses. The study of caffeine from the gel preparation was carried out using a Franz diffusion cell. Caffeine content in the gel preparation and its release are determined by spectrophotometric method. The results showed that the amount of HPMC used would increase the viscosity value (+14113.92) and decrease the spreadability (-0.29) and pH (-6.59167E-003) of the gel. The greater the amount of propylene glycol used will decrease the viscosity value (-2484.54) and increase the spreadability value (+0.30) and pH (+0.31802) of the gel. The conclusion of this study is the use of a combination of HPMC and propylene glycol (6%:17%) resulted in the optimum formula with a viscosity value of 44,070 cps, a spreadability value of 3.6 cm, and a pH value of 5.32. The caffeine content obtained in the gel preparation was 188.47 g and the amount of caffeine released from the gel preparation for 6 hours of testing was 4.95%.